Factors limiting exercise capacity in COPD patients - Djebaili, R.; Righi, N.; Benbouza, A.; Chiboub, B. (International Journal of Medicine, 2024)
Introduction: Impaired exercise capacity in COPD patients leads to deterioration in their physical activity and quality of life. The aim of our study was to assess the exercise capacity of COPD patients using the 6-minute walk test (6MWT) and to determine the factors limiting their exercise capacity.Methods: Stable COPD patients were included in this study to assess their exercise capacity using the 6-minute walk test (6MWT) and to investigate the relationship between exercise capacity, functional status (FEV1), quadriceps muscle dysfunction (strength and endurance), and fat free mass index (FFMI).Results: 175 COPD patients (166 males and 9 females) aged between 40 and 86 years with a mean age of 67.95 years. The functional stages distribution according to GOLD was GOLDI: 19.43%, GOLDII: 30.29%, GOLDIII: 33.71%, GOLD IV: 16.57%. 25% of patients received long-term oxygen therapy (LTOT). The mean distance covered by COPD patients was 432.26 ± 129.731 meters, corresponding to 64.71 ± 19.04%. 56 (32%) COPD patients had exercise intolerance as assessed by the distance walked over 6 minutes (6MWD). A significant correlation was found between the 6MWD, quadriceps endurance (P<0.000) and FEV1 (p<0.002), whereas no correlation was found with MVC (P<0.039) and (FFMI) (P<0.062).Conclusion: Muscle dysfunction and the severity of bronchial obstruction are the factors most associated with impaired exercise capacity in COPD patients.